2008
DOI: 10.1128/aac.01136-07
|View full text |Cite
|
Sign up to set email alerts
|

Zygomycetes Hyphae Trigger an Early, Robust Proinflammatory Response in Human Polymorphonuclear Neutrophils through Toll-Like Receptor 2 Induction but Display Relative Resistance to Oxidative Damage

Abstract: Human polymorphonuclear neutrophils (HPMNs) displayed attenuated hyphal damage associated with impaired O 2 ؊ release following exposure to Rhizopus oryzae versus that with Aspergillus fumigatus. Exposure of HPMNs to R. oryzae hyphae resulted in upregulation in Toll-like receptor 2 mRNA and a robust proinflammatory gene expression with rapid (1-h) induction of NF-B pathway-related genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 14 publications
2
82
0
2
Order By: Relevance
“…Invasive fungal growth activates pro-inflammatory signaling. Hyphae interact with TLR-2 on the surface of human PMNs inducing transcription of the proinflammatory cytokines TNF-α and IL-1β [14]. Human monocyte derived dendritic cells recognize β-glucan exclusively expressed on the hyphal surface through the pattern recognition receptor dectin-1 to induce IL-23, IL-1 and TNF-α [15].…”
Section: Innate Immune Responses During Mucormycosismentioning
confidence: 99%
“…Invasive fungal growth activates pro-inflammatory signaling. Hyphae interact with TLR-2 on the surface of human PMNs inducing transcription of the proinflammatory cytokines TNF-α and IL-1β [14]. Human monocyte derived dendritic cells recognize β-glucan exclusively expressed on the hyphal surface through the pattern recognition receptor dectin-1 to induce IL-23, IL-1 and TNF-α [15].…”
Section: Innate Immune Responses During Mucormycosismentioning
confidence: 99%
“…Although inactive spores do not induce neutrophil migration, active spores and hyphae present a potent chemotactic signal (Waldorf and Diamond 1985). After encountering R. oryzae hyphae, human polymorphonuclear neutrophils activate the expression of Toll-like receptor 2 and NF-kB pathwayrelated genes (Chamilos et al 2008b). Additionally, Dectin-1-dependent activation of interleukin 23 production by human dendritic cells induces proinflammatory Th17 responses (Chamilos et al 2010).…”
Section: Host Factors In Mucormycosismentioning
confidence: 99%
“…A recent report with A. fumigatus and Rhyzopus oryzae hyphae has shown that this process is probably regulated by pathogen recognition systems. Human PMNs produced equivalent amounts of superoxide anion in response to both, but released larger quantities of ROS when challenged with A. fumigatus [48].…”
Section: Non-phagocytic Killingmentioning
confidence: 99%